Literature without borders - Sobczak, Izabela (Porównania, 2022)
This article is a review of the work Dezorientacje. An Anthology of Polish Queer Literature edited by Alessando Amenta, Tomasz Kaliściak and Błażej Warkocki, which was published in 2021. The anthology is an extensive collection of excerpts from both canonical and marginal works of Polish literature. Representing a variety of themes, authors and genres from the eighteenth century to the present day, the anthology casts a new, unprejudiced light on the historical literary tradition, destabilizing the separatist divisions into center and periphery, high and low, male and female, which have hitherto shaped the canon of Polish literature. Thus Polish readers will find a work without prejudice and without borders, open to additions and new interpretations, but developed on the basis of queer theory and itself queer in its content and methodology of selection. Amenta, Kaliściak, and Warkocki capture the canon with subversive potential, creating an anthology that can be read both as a textbook and as a coherent, multithreaded narrative.